2022
DOI: 10.1159/000521684
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features of Incidentally Diagnosed Urothelial Bladder Cancer: A Retrospective Data Analysis

Abstract: <b><i>Introduction:</i></b> The aim of this study was to evaluate the prevalence and clinical features of incidental bladder cancer (BC) diagnosis, with special emphasis on possible associations between incidental diagnosis and primary disease stage or grade. <b><i>Methods:</i></b> We retrospectively included 501 consecutive patients who underwent transurethral resection of bladder tumor and were diagnosed with primary urothelial carcinoma of the bladder between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Our study revealed that asymptomatic patients who were incidentally diagnosed through imaging studies or identified during the evaluation of asymptomatic microscopic hematuria exhibited more favorable histopathological and morphological bladder cancer features compared to symptomatic patients. While previous studies have established an association between symptomatic presentation and a more advanced bladder cancer grade and stage, our study adds novel insights by identifying additional factors of interest, including the presence of concomitant CIS, larger tumor size, and increased number of tumors [ 14 , 15 ]. These findings may be attributed to the early detection of bladder cancer in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study revealed that asymptomatic patients who were incidentally diagnosed through imaging studies or identified during the evaluation of asymptomatic microscopic hematuria exhibited more favorable histopathological and morphological bladder cancer features compared to symptomatic patients. While previous studies have established an association between symptomatic presentation and a more advanced bladder cancer grade and stage, our study adds novel insights by identifying additional factors of interest, including the presence of concomitant CIS, larger tumor size, and increased number of tumors [ 14 , 15 ]. These findings may be attributed to the early detection of bladder cancer in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent retrospective studies have investigated incidentally diagnosed bladder cancer and compared the pathological features of incidental cases detected through imaging techniques with symptomatic cases. In both studies, the criteria for defining study groups slightly differed from ours, as they included patients with microscopic hematuria in the symptomatic group [ 14 , 15 ]. Since microscopic hematuria without additional symptoms is a sign of a potential disease observed by a physician, rather than a symptom, we classified patients with microscopic hematuria into the asymptomatic group [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As no standardized screening algorithm for bladder cancer detection currently exists, systematic opportunistic screening for bladder abnormalities would represent a paradigm shift among radiologists, potentially facilitating early diagnosis [44]. We believe that during abdominopelvic imaging performed for alternative indications, a concentrated bladder survey could significantly aid in bladder cancer detection, particularly in highrisk patients (those over 50 years of age, especially patients with a history of tobacco abuse and/or industrial chemical exposures).…”
Section: Discussionmentioning
confidence: 99%